Methods for infection prevention in the built environment—a mini-review - Salonen, Noora; Ahonen, Merja; Sirén, Kai; Mäkinen, Riika; Anttila, Veli-Jukka; Kivisaari, Meija; Salonen, Kalle; Pelto-Huikko, Aino; Latva, Martti (Frontiers in Built Environment, 2023)
The COVID-19 pandemic has shown that infection prevention actions need to be more efficient in public indoor environments. In addition to SARS-CoV-2, the cause of COVID-19, many pathogens, including other infectious viruses, antibiotic-resistant bacteria, and premise plumbing pathogens, are an invisible threat, especially in public indoor spaces. The indoor hygiene concept for comprehensive infection prevention in built environments highlights that the indoor environment should be considered as a whole when aiming to create buildings with increased infection prevention capacity. Within indoor environments, infections can indirectly spread through surfaces, air, and water systems. Many methods, such as antimicrobial technologies and engineering solutions, targeting these indoor elements are available, which aim to increase the hygiene level in indoor environments. The architectural design itself lays a foundation for more efficient infection prevention in public buildings. Touchless solutions and antimicrobial coatings can be applied to frequently touched surfaces to prevent indirect contact infection. Special ventilation solutions and air purification systems should be considered to prevent airborne infection transmissions. Proper design and use of water supply systems combined with water treatment devices, if necessary, are important in controlling premise plumbing pathogens. This article gives a concise review of the functional and available hygiene-increasing methods—concentrating on indoor surfaces, indoor air, and water systems—to help the professionals, such as designers, engineers, and maintenance personnel, involved in the different stages of a building’s lifecycle, to increase the infection prevention capacity of public buildings.